HEAT CAPACITY OF CRYSTALS. EXPLANATION OF THE TEMPERATURE DEPENDENCE OF HEAT CAPACITY - Bozorov Nosirzhon Sodikovich; Umurkulov Kayumjon Parpievich; Alisherov Otabek Alisher coals; Zhaloliddinova Sarvigul Odiljon kizi (Galaxy International Interdisciplinary Research Journal, 2024)
The article outlines the main applications of the heat capacity of crystalline bodies. From the standpoint of classical theory , it is impossible to explain the dependence of heat capacity on temperature. Between the regions of low and high temperatures lies a fairly wide region of socalled average temperatures, in which there is a gradual transition from Debye’s law to Dulong and Petit’s law .